Kontribusi konsep diri terhadap perencanaan karier siswa - Dian Rahmawati; Rezky Permata Sari; Afiatin Nisa (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
career planning was an important component in students' career development. One thing that is thought to have an effect on students' career planning is self-concept. The aim of this study was to determine whether self-concept affects the career planning of SMKS Muhammadiyah 11 Jakarta students. The research is a quantitative research with a survey type. The population in this study were 394 students. The sample was drawn by simple random sampling with a sample size of 39 students. Data were collected through a questionnaire. Data were analyzed using simple linear regression test. The results showed that a). Students' self-concept is in the medium category, b) students' career planning is in the high category, and c) self-concept has a significant effect on career planning of students at SMKS Muhammadiyah 11 Jakarta